Wprowadzenie kontroli konstytucyjności ustaw a posteriori we Francji – geneza, cele i skutki reformy 2008 .......... 35 - Popardowska, Anna (Współczesne zmiany konstytucji w wybranych państwach europejskich: Pomiędzy partykularyzmem prawnym a wspólnotą doświadczeń, 2025)
INTRODUCTION OF A POSTERIORI CONSTITUTIONAL REVIEW OF LAWS IN FRANCE – ORIGINS, OBJECTIVES AND EFFECTS OF THE 2008 REFORMThe amendment to the Constitution of the Fifth French Republic of 23 July 2008, introducing a posteriori constitutional review of legislation, represented a significant step in the development of the French system of constitutional protection. The aim of this study is to determine whether this change was a response to internal challenges or whether it reflected broader European trends in constitutional reform. The analysis focuses on the evolution and functioning of the Constitutional Council and the changes introduced by the 2008 amendment, as well as the broader context of the reform: its causes, objectives, and institutional implications. As a result of the reform, the Council acquired a more judicial character and shows certain similarities to European solutions, particularly regarding the shared goal of protecting human rights, erga omnes effects, and a posteriori review. However, the Council’s unique system of filters and its specific composition constitute a distinct French legal particularism. The reform was primarily a response to the domestic deficit in effective constitutional review and the need to strengthen the supremacy of the Constitution.